The Practice of Interactive Teaching Methods in the Introduction to Sociology Course at Regional Second-Tier Universities in China - Liu, Moxian; Zhang, Yilie (Journal of Educational Research and Policies, 2024)
Traditional teaching methods for the Introduction to Sociology Course at regional second-tier universities often emphasize theory over practice, lacking a focus on fostering students' critical thinking and practical skills. Interactive teaching methods address these shortcomings by emphasizing the dynamic interaction between teachers and students as well as among students themselves. This paper explores a teaching reform practice centered on the theme of "sociological imagination," detailing the implementation process in the classroom. The findings demonstrate that interactive teaching methods significantly enhance students' enthusiasm for learning, deepen their understanding of sociological concepts and theories, and improve their critical thinking and problem-solving skills. It is recommended to integrate technological tools to optimize classroom experiences, introduce role-playing activities, and further refine the teaching evaluation mechanisms.